Physical exercise in the prevention and treatment of Alzheimer's disease - Adrian De la Rosa; Gloria Olaso-Gonzalez; Coralie Arc-Chagnaud; Fernando Millan; Andrea Salvador-Pascual; Consolacion García-Lucerga; Cristina Blasco-Lafarga; Esther Garcia-Dominguez; Aitor Carretero; Angela G. Correas; Jose Viña; Mari Carmen Gomez-Cabrera (Elsevier, 2020)
Dementia is one of the greatest global challenges for health and social care in the 21st century. Alzheimer's disease (AD), the most common type of dementia, is by no means an inevitable consequence of growing old. Several lifestyle factors may increase, or reduce, an individual's risk of developing AD. Much has been written over the ages about the benefits of exercise and physical activity. Among the risk factors associated with AD is a low level of physical activity. The relationship between physical and mental health was established several years ago. In this review, we discuss the role of exercise (aerobic and resistance) training as a therapeutic strategy for the treatment and prevention of AD. Older adults who exercise are more likely to maintain cognition. We address the main protective mechanism on brain function modulated by physical exercise by examining both human and animal studies. We will pay especial attention to the potential role of exercise in the modulation of amyloid β turnover, inflammation, synthesis and release of neurotrophins, and improvements in cerebral blood flow. Promoting changes in lifestyle in presymptomatic and predementia disease stages may have the potential for delaying one-third of dementias worldwide. Multimodal interventions that include the adoption of an active lifestyle should be recommended for older populations.